Tác động kinh tế của biến đổi khí hậu đến ngành đánh cá Việt Nam - Le Van , Chon; Nguyen Manh, Hung; Nguyen Thi Lan , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Aquaculture is an important economic sector in Vietnam accounting for 3.07% of GDP, though suffering directly from weather conditions and natural disasters. Employing a panel data set of 28 coastal provinces from 2002 to 2018 period, the paper evaluates the impacts of climate change including natural disasters and weather conditions on capture fisheries production in Vietnam. It finds that precipitation and tropical depressions do not have significant effects on fish catch. In addition, an interesting result is that storms and average wind speed increase the amount of capture fisheries, holding other things constant. Based on the research of the influences of climate change on fish catch, the paper proposes several policy implications in sustainable management of fisheries subsector in response to changes in natural disasters and weather conditions.